Application of diffracted wave analysis to time-lapse seismic monitoring of CO2 geosequestration - Alonaizi, Faisal (Curtin University, 2014)
Successful implementation of carbon capture and sequestration technology requires monitoring techniques for tracking CO2 plume evolution in the subsurface and early leakage detection. Application of time-lapse seismic data for these purposes can often be challenging in low signal/noise ratio conditions. The research is focussed on developing a robust seismic imaging algorithm for CO2 geosequestration monitoring, based on diffracted waves analysis. The algorithm is tested on several datasets, including CO2CRC Otway project time-lapse seismic data.